Family and Caregiving Issues. (11th November 2018) - Chi, W; Graf, E; Karon, S
Abstract: Due to long care hours and physically demanding caregiving, several family members often share caregiving responsibilities for community-dwelling persons with dementia (PwD). Yet, little is known about the types of informal care provided and impact of caregiving on informal caregivers by relationship to care recipients using a national sample in United States. We studied a nationally representative sample of 679 Medicare beneficiaries with dementia and their informal caregivers (n=1, 467) using the 2015 National Health and Aging Trends Study (NHATS) and National Study on Caregiving (NSOC) survey. We examined total hours of care per month and the types of care provided. Impact of caregiving was measured as emotional or physical difficulties, and work productivity loss (WPL). Generalized linear and logistic regression models controlling for PwD's age, gender, and impairment were used. With analytical weights, 5.7 million informal caregivers provided care to 4.0 million PwD. Despite spousal and children caregivers were equally likely to provide help in medical care, transportation, and mobility, spousal caregivers provided the most care hours per month, followed by daughters (96 and 59 more hours per month than sons, respectively). Compared to spousal caregivers, daughters were more likely to report emotional difficulty (aOR=3.8, p<0.01); whereas sons were less likely to report physical difficulty (aOR=0.1, p<0.01). Daughters had the greatest WPL (8.1%). Daughters provided the second most care hours and were more likely to have a negative impact from informal caregiving than spouses and sons. Policymakers need to allocate resource to alleviate negative caregiving impacts to daughters.